Recent advances in genome editing and creation of genetically modified pigs. (November 2015) - Butler, James R.; Ladowski, Joseph M.; Martens, Gregory R.; Tector, Matthew; Tector, A. Joseph
Abstract: The field of xenotransplantation is benefiting greatly from recent advances in genetic engineering. The efficiency and pace with which new model animals are being created has dramatically sped progress towards clinical relevance. Endonuclease-driven genome editing now allows for the efficient generation of targeted genetic alterations. Herein we review the available methods of genetic engineering that have been successfully employed to create genetically modified pigs. Highlights: Relying on homologous recombination, the creation of gene-targeted pigs was originally slow and tedious. 2000, somatic cell nuclear transfer (SCNT) was successfully used to clone pigs. 2013, ZFN were used to create a biallelic knockout of both the GGTA1 and CMAH genes in vitro prior to SCNT. 2013, clustered randomly interspaced short palindromic repeats and the associated protein 9 (CRISPR/Cas9) were introduced. 2015 CRISPR/Cas9 system has been used to simultaneously silence 3 genes.